2019
DOI: 10.1002/chir.23069
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of novel chiral metal complexes derived from chiral thiosemicarbazide ligands as potential antioxidant agents

Abstract: Two new chiral thiosemicarbazide ligands and their Cu (II), Ni (II), Pd (II), and Zn (II) complexes were synthesized and characterized by nuclear magnetic resonance (NMR) (only for ligand), Fourier transform infrared (FT‐IR), ultraviolet visible (UV‐Vis), mass, and elemental analysis. The antioxidant activity of ligands and their metal complexes was examined. It was found that the antioxidant activity of metal complexes was better than their ligands. In addition, the antioxidant activity, as reflected by free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…The NH (H-6, H-7, and H-9) protons of thiosemicarbazide (-NH-NH-C=S-NH-) derivatives 1-12 were detected at δ 9.11-10.03, 10.34-11.29, and 9.55-10.52 ppm, respectively. In the a study [25], 1 H NMR protons data in the thiosemicarbazide scaffold were found to be compatible with the chemical shift values of thiosemicarbazide protons in this study. The resonance of proton H-7 in the 1,2,4-triazole derivatives at 13.97-14.22 ppm and the disappearance of the H-6 and H-9 protons in the thiosemicarbazide derivatives in the cyclization products were de nite evidence of the synthesis of 1,2,4-triazole derivatives.…”
Section: Chemistrysupporting
confidence: 86%
“…The NH (H-6, H-7, and H-9) protons of thiosemicarbazide (-NH-NH-C=S-NH-) derivatives 1-12 were detected at δ 9.11-10.03, 10.34-11.29, and 9.55-10.52 ppm, respectively. In the a study [25], 1 H NMR protons data in the thiosemicarbazide scaffold were found to be compatible with the chemical shift values of thiosemicarbazide protons in this study. The resonance of proton H-7 in the 1,2,4-triazole derivatives at 13.97-14.22 ppm and the disappearance of the H-6 and H-9 protons in the thiosemicarbazide derivatives in the cyclization products were de nite evidence of the synthesis of 1,2,4-triazole derivatives.…”
Section: Chemistrysupporting
confidence: 86%
“…DPPH free radical scavenging and ABTS cation radical scavenging assays were conducted as described by Ferreira et al (2014). The procedure defined by Başaran et al (2019) was used to determine the β-Carotene-linoleic acid and cupric reducing antioxidant capacity (CUPRAC) of films with some adjustments. Solutions of films were prepared at 50, 25, 12.5 and 6.25 ppm concentrations.…”
Section: Determination Of Antioxidant Activitymentioning
confidence: 99%
“…Thus, the sulfur atom can bind to the metal in its thione form or in its thiolate form [29][30][31]. There are also complexes in which the sulfur atom remains uncoordinated [32,33]. In this article, we report the synthesis and structural characterization of the Co(II/III), Ni(II) and Zn(II) complexes of 1-(1-hydroxypropan-2-ylidene)thiosemicarbazide (H2L) (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%